Decontamination of equipment with oil and gas NORM: the need for internal individual monitoring - A. C. C. S. Ribeiro; W. O. Sousa; F. C. A. Silva (Brazilian Journal of Radiation Sciences, 2024)
In the oil field, Naturally Occurring Radioactive Material - NORM is present in petroleum-forming rocks and this is related to the presence of radioactive decay series of 238U and 232Th, mainly the daughter radionuclides 226Ra and 228Ra. These radionuclides are detected during the process of production and extraction of oil and gas. They migrate from the reservoir rock and flow through the production lines until the operating areas, forming sludge and scale. The presence of 226Ra and 228Ra can be found in many pieces of equipment on the platforms, and NORM concentrations may increase due to different extraction processes. When this accumulation of NORM occurs inside the equipment, it is necessary to decontaminate them. Depending on the decontamination technique, workers can be exposed to radioactive materials contained in sludge and scale, which are released in the form of aerosols. The existing radiological risk during decontamination is based on external irradiation and internal contamination of workers, this is why an individual monitoring program covering both external and internal dosimetry is necessary. External monitoring is widely used during the routine work of decontamination of equipment, but for internal monitoring, the real importance has not been given, despite the probability of being the greatest contribution to radiological risk for workers. This article presents the need for internal individual monitoring for a comprehensive assessment of radiological risk and a general description of how it is being done in several countries to assist in the implementation of a complete individual monitoring program, mainly in Brazil.